Club deals in leveraged buyouts - Officer, Micah S.; Ozbas, Oguzhan; Sensoy, Berk A. (Journal of Financial Economics, 2010)
We analyze the pricing and characteristics of club deal leveraged buyouts (LBOs)—those in which two or more private equity partnerships jointly conduct an LBO. Using a comprehensive sample of completed LBOs of U.S. publicly traded targets conducted by prominent private equity firms, we find that target shareholders receive approximately 10% less of pre-bid firm equity value, or roughly 40% lower premiums, in club deals compared to sole-sponsored LBOs. This result is concentrated before 2006 and in target firms with low institutional ownership. These results are robust to controls for target and deal characteristics, including size, Q, measures of risk, and time and industry fixed effects. We find little support for benign motivations for club deals based on capital constraints, diversification motives, or the ability of clubs to obtain favorable debt amounts or prices, but it is possible that the lower pricing of club deals is an inadvertent byproduct of an unobserved benign motivation for club formation.